Are trade-law inspired investment rules desirable? - Marino Baldi (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
While bilateral investment treaties have traditionally focused on investment protection, modern investment agreements have increasingly included rules on liberalization and development, such as sustainable investment. Given the complexities of negotiating all these elements under one instrument, we should consider a multiple-instruments solution.
Keywords: 330